2015
DOI: 10.30843/nzpp.2015.68.5827
|View full text |Cite
|
Sign up to set email alerts
|

Risks to pest management in New Zealands pipfruit Integrated Fruit Production programme

Abstract: Pest management in New Zealand's pipfruit Integrated Fruit Production (IFP) programme relies on selective pesticides, biological control and pheromone mating disruption. The current situation is potentially precarious and one concern, the impact of less selective pesticides, was tested. Apple trees received synthetic pyrethroid (deltamethrin) sprays during the first half of two growing seasons. Beneficial and pest species were monitored monthly from November to April. Treated trees had fewer predatory bugs (91… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…This WAA case study highlights the vulnerability of the IFP programme in New Zealand apple orchards where pest control is reliant on a limited number of control measures. Other pipfruit pests such as mites, mealybugs and apple leafcurling midge are also subject to disruption (Lo et al 2015). The cause of the disruption can be biological or agrichemical, and can include new pests and diseases, changes in resistance status, loss of registered products and changes in legislation.…”
Section: Discussionmentioning
confidence: 99%
“…This WAA case study highlights the vulnerability of the IFP programme in New Zealand apple orchards where pest control is reliant on a limited number of control measures. Other pipfruit pests such as mites, mealybugs and apple leafcurling midge are also subject to disruption (Lo et al 2015). The cause of the disruption can be biological or agrichemical, and can include new pests and diseases, changes in resistance status, loss of registered products and changes in legislation.…”
Section: Discussionmentioning
confidence: 99%
“…Chlorpyrifos, tebuconazole, and beta-cypermethrin are widely used in orchard management in many developing countries for insecticidal and bactericidal purposes. 8) However, due to the lack of proper supervision and management, the use of pesticides far exceeds the recommended level, and some studies have found that, after the phosphorus-oxygen bond on chlorpyrifos is broken, the formation of 3,5,6-TCP is riskier than the parent pesticide. Pyrethroid pesticides are widely used, and their degradation product, 3-PBA, can cause agricultural product secondary pollution.…”
Section: Introductionmentioning
confidence: 99%
“…Based on recent modelling approaches, as well as newly reported distribution points, its dispersal will likely continue in the coming years. The brown marmorated stink bug is considered a major biosecurity concern for Australia and New Zealand [22,23,24]. In the new regions of its introduction in North America and Europe, it has become a devastating pest, causing significant damage and economic loss, as well as creating nuisance to residents in rural and urban areas [25].…”
Section: Introductionmentioning
confidence: 99%